Hidrogéis de colágeno extraído de pele de tilápia do Nilo com potencial aplicação na engenharia de tecidos - Menezes, Maria do Livramento Linhares Rodrigues (2020)
Nile tilapia skin, an abundant waste from fish processing, can be used for collagen extraction, which has a high aggregated value for biomedical applications. Collagen extraction was conducted under different reaction conditions (time, temperature, and concentration of acetic acid) in order to optimize the yield without compromising the integrity of the collagen. Temperature and time were responsible for increased yield. The extraction at 4 ºC (Col-4) and 20 ºC (Col-20) produced the acid-solubilized collagen (ASC) with the intact triple helix and was analysed by Fourier-transform infrared spectroscopy (FT-IR) and circular dichroism (CD). Col-4 and Col-20 was also characterized by hydroxyproline, degree of recovery and temperature of denaturation by viscometry. The collagen obtained in the optimized reaction conditions (which used 0.35 mol/L of acetic acid at 20 °C and time 65 hours) was used to obtain for the first-time fish-based hydrogels with hyaluronic acid (HA) crosslinked with 1-ethyl-3-(3-dimethylaminopropryl carbodiimide (EDC) and N- hydroxysuccinimide (NHS). The hydrogels were obtained using different concentration ratios of the crosslinkers (EDC and NHS) and were characterized by scanning electron microscopy (SEM), rheology, degree of swelling, enzymatic degradation, FT-IR, Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The hydrogel with the highest crosslinking efficiecy presented a robust organized network, swells 255% in PBS and bears interconnected pores with a diameter in the range of 10- 100 µm. The best hydrogel was incorporated with thymol in different concentrations (0.25-0.5 and 1%). Hydrogels incorporated with thymol were characterized by antimicrobial activity, antioxidant activity, cytotoxicity and FT-IR. The hydrogels of Col-AH-Timol_0.25 and Col-AH-Timol_0.5 did not show antimicrobial activity. The hydrogel Col-AH-Timol_1.0 showed antimicrobial activity, however, it showed reduced cell viability. However, the hydrogel reticulated with EDC and NHS showed improved cell viability, indicating its safe use for the biomedical área.